2015
DOI: 10.1165/rcmb.2014-0256rc
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals an Altered Cystic FibrosisIn VitroBronchial Epithelial Secretome

Abstract: Alterations in epithelial secretions and mucociliary clearance contribute to chronic bacterial infection in cystic fibrosis (CF) lung disease, but whether CF lungs are unchanged in the absence of infection remains controversial. A proteomic comparison of airway secretions from subjects with CF and control subjects shows alterations in key biological processes, including immune response and proteolytic activity, but it is unclear if these are due to mutant CF transmembrane conductance regulator (CFTR) and/or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 79 publications
5
42
0
Order By: Relevance
“…Approximately half of these proteins (53%) were significantly different in abundance between genotypes, with 80% being increased in CF. This finding is similar to those of a recent study evaluating the ASL proteome of CF and non-CF HBE cultures, which demonstrated that the majority of differentially expressed proteins was elevated in CF (26). An unexpected finding was the inclusion of many intracellular proteins and membrane-associated proteins ( Figure 1D), with only 25.6% (z668 protein) of the total 2,608 proteins being classified as known secreted proteins (27) (Figure 1E, Table E2B).…”
Section: Defining the Smg Secretome From Cf And Non-cf Airways Using supporting
confidence: 89%
“…Approximately half of these proteins (53%) were significantly different in abundance between genotypes, with 80% being increased in CF. This finding is similar to those of a recent study evaluating the ASL proteome of CF and non-CF HBE cultures, which demonstrated that the majority of differentially expressed proteins was elevated in CF (26). An unexpected finding was the inclusion of many intracellular proteins and membrane-associated proteins ( Figure 1D), with only 25.6% (z668 protein) of the total 2,608 proteins being classified as known secreted proteins (27) (Figure 1E, Table E2B).…”
Section: Defining the Smg Secretome From Cf And Non-cf Airways Using supporting
confidence: 89%
“…CF ASN is characterized by an abnormal molecular composition (including altered lactate, small metabolite, and protein contents), itself caused by altered epithelial function, and the sustained presence of bacteria and PMNs in the CF airway lumen . It is interesting to note that at concentrations similar to those used to promote PMN transmigration and conditioning in our model, CF ASN induces T cell apoptosis .…”
Section: Discussionmentioning
confidence: 90%
“…CF mouse models, which often lack airway obstruction and spontaneous infection, consistently demonstrate heightened and prolonged inflammatory responses in the airway after a disease relevant challenge (e.g., bacteria or bacterial products), supporting the concept of primary alterations in host response . Likewise, a reductionist approach to this question, through use of isolated cells studied in vitro, has repeatedly shown altered inflammatory signaling both with and without infectious challenge . Human CF fetal tracheal grafts implanted into an animal model produced eight times more IL‐8, a potent neutrophil chemoattractant, than did non‐CF fetal tracheal grafts .…”
Section: Associations Between Abnormal Cftr and Airway Inflammationmentioning
confidence: 88%